Integrating Student Self-Assessment as a Key Instrument for Achieving Need-Supportive Learning Outcomes - Hidayati, Dewi (Nexus Publishing NXP, 2024)
Promoting effective academic assessment in higher education presents substantial challenges, particularly in aligning assessment practices with need-supportive teaching to enhance student outcomes. This study proposes the strategic integration of student self-assessment (SSA) as a central tool to address these challenges, focusing on its impact on academic performance at STAI Diponegoro Tulungagung, Indonesia. Through a correlational design, the research examines the influence of SSA on the students’ learning outcomes, specifically within the “English for Beginner” (EfB) course. A series of tests and an adapted SSA questionnaire were employed to measure the effects of consistent self-evaluation. The findings reveal that SSA practices significantly strengthen the connection between guided instruction and independent student achievement. Engaging instructional methods and structured participation were found to enhance student involvement, leading to improved self-assessment and better academic outcomes. These results underscore SSA’s role as a behavioral mechanism that not only clarifies but also empirically supports the link between need-supportive teaching practices and student success. By embedding SSA into routine educational assessments, educators can gain nuanced insights into individual learning needs, allowing for the adaptation of teaching strategies to better support student engagement and achievement. The implications of these findings are profound, suggesting that SSA has the potential to transform academic engagement and success in higher education. Future research should investigate the applicability of SSA across different subjects and educational settings to further explore its capacity to improve learning outcomes on a broader scale.